Transcription factor‐microRNA associations and their impact on colorectal cancer survival. Issue 11 (3rd August 2017) - Mullany, Lila E.; Herrick, Jennifer S.; Wolff, Roger K.; Stevens, John R.; Samowitz, Wade; Slattery, Martha L.
Abstract : MicroRNAs (miRNAs) and Transcription Factors (TFs) both influence messenger RNA (mRNA) expression, disrupting biological pathways involved in carcinogenesis and prognosis. As many miRNAs target multiple mRNAs, thus influencing a multitude of biological pathways, deciphering which miRNAs are important for cancer development and survival is difficult. In this study, we (i) determine associations between TF and survival ( N = 168 colon cancer cases); (ii) identify miRNAs associated with TFs related to survival; and (iii) determine if factors derived from TF‐specific miRNA principal component analysis (PCA) influence survival. Cox Proportional hazard models were run for each PCA factor to determine Hazard Ratios (HR) and 95% Confidence Intervals (CI) adjusting for age, center, and AJCC stage. Thirty TFs improved survival when differential expression increased; 27 of these were associated significantly with normal colonic mucosa expression of 65 unique miRNAs when an FDR q ‐value of <0.05 was applied. Five factors, comprising 21 miRNAs, altered survival in rectal cancer subjects; four of these five factors improved survival and one factor reduced survival. One factor comprising four miRNAs reduced survival in colon cancer subjects. In summary, our data suggest that expression of TFs and their related miRNAs influence survival after diagnosis with colorectal cancer.